Eosin Yellowish Dye-Sensitized ZnO Nanostructure-Based Solar Cells Employing Solid PEO Redox Couple Electrolyte. (11th March 2012) - Kanmani, S. S.; Ramachandran, K.; Umapathy, S.
Abstract : ZnO nanostructures are synthesized by low-temperature methods, and they possess polycrystalline hexagonal wurtzite structure with preferential c-axial growth. Morphological study by SEM shows the presence of ~ 30 nm sized spherical-shaped ZnO nanoparticle, the branched flower-like ZnO composed of many nanorods (length: 1.2 to 4.2  μ m and diameter: 0.3 to 0.4  μ m), and ~ 50 nm diameter of individual ZnO nanorods. Reduction in photoemission intensity of nanorods infers the decrease in electron-hole recombination rate, which offers better photovoltaic performance. The dye-sensitized solar cell (DSSC) based on ZnO nanorods sensitized with Eosin yellowish dye exhibits a maximum optimal energy conversion efficiency of 0.163% compared to that of nanoparticles and nanoflowers, due to better dye loading and direct conduction pathway for electron transport.